Determinants of Online Donation Decisions through Mobile Banking - Desy Khairani; Nurhalimah Lubis; Syarifah Isnaini (Verba: Journal of Applied Linguistics, 2022)
The people of Padangsidimpuan Tenggara District are no strangers to the mobile banking application which has a feature to donate, but the majority of the people still decide to donate in person rather than online.  The formulation of the problem in this study is whether there is a partial and simultaneous effect of trust, convenience and religiosity on the decision to donate online through mobile banking.  This study aims to determine whether there is a partial and simultaneous effect of trust, ease and religiosity on the decision to donate online through mobile banking.The theory used in this study relates to online donation decisions, trust, convenience and religiosity.  The decision to donate online is a conclusion from the problem-solving process to make a donation.  Trust is a person's belief that when someone makes a decision, he will choose a trust based on the choice of the person he trusts.  Convenience explains that if a technology is easy to use then users tend to use the technology.  Religiosity is an attitude to bind oneself in relation to God.This research is a quantitative research.  Sampling by incidental technique with a total sample of 80. Data collection used a questionnaire (questionnaire), interviews, and documentation.  Analysis of the data used by testing the validity, reliability, normality, classical assumption test, partial test (t test), simultaneous test (f test) and multiple linear regression analysis, the data is processed with the help of the SPSS version 23 program.The results of this study indicate that there is an effect of trust on the decision to donate online through mobile banking, there is an effect of convenience on the decision to donate online through mobile banking, there is no influence of religiosity on the decision to donate online through mobile banking, there is an influence of trust, convenience, religiosity simultaneously on the decision  donate online via mobile banking.  These factors can be considered for Islamic banks to increase customers.